Homocysteine: validation and comparison of two methods using samples from patients with pulmonary hypertension - Barbosa,Tatiana Maria Costa de Campos (2014)
Introduction and objective:The determination of homocysteine plasma levels has been reported as a risk marker of interest in severe diseases involving endothelial injury and associated with the development or progression of atherosclerotic lesions and thrombus formation. The aims of this study were to validate method for quantification of plasma homocysteine by high performance liquid chromatography (HPLC) with fluorimetric detection, and to compare the results obtained from patients with pulmonary hypertension by HPLC with those obtained by spectrophotometric enzymatic cycling (S-Ec) method.Materials and methods:The validation parameters, such as linearity, matrix effect, precision, accuracy, detection and quantitation limits, and robustness of the method were evaluated aiming to demonstrate that it is suitable for the intended use. The data obtained in the quantification of homocysteine using the validated method (HPLC) and the spectrophotometric enzymatic cycling (S-Ec) method, were compared.Results:The method was precise, accurate, and robust; it also had good recovery and showed no matrix effect. The linearity covered a range of 5.0-85.0 µmol/l and the limits of detection and quantification were 1.0 µmol/l and 3.4 µmol/l, respectively. The results obtained for homocysteine determination by HPLC and S-Ec methods were comparable.Conclusion:The validated HPLC method showed good performance for quantification of plasma homocysteine levels, while S-Ec method provided results for homocysteine comparable with those obtained by the validated method; therefore, this methodology is a potential alternative of automated method for clinical laboratories.